IDH Mutation Subgroup Status Associates with Intratumor Heterogeneity and the Tumor Microenvironment in Intrahepatic Cholangiocarcinoma. Issue 17 (11th July 2021) - Xiang, Xiao; Liu, Ziyang; Zhang, Chong; Li, Zhao; Gao, Jie; Zhang, Changkun; Cao, Qi; Cheng, Jinghui; Liu, Hengkang; Chen, Dingbao; Cheng, Qian; Zhang, Ning; et al.
Abstract: Intrahepatic cholangiocarcinoma (ICC) is highly heterogeneous. Here, the authors perform exome sequencing and bulk RNA sequencing on 73 tumor regions from 14 ICC patients to portray the multi‐faceted intratumor heterogeneity (ITH) landscape of ICC. The authors show that ITH is highly concordant across genomic, transcriptomic, and immune levels. Comparison of these data to 8 published datasets reveals significantly higher degrees of ITH in ICC than hepatocellular carcinoma. Remarkably, the authors find that high‐ITH tumors highly overlap with the IDH (isocitrate dehydrogenase)‐mutant subgroup ( IDH ‐SG), comprising of IDH ‐mutated tumors and IDH ‐like tumors, that is, those IDH ‐wildtype tumors that exhibit similar molecular profiles to the IDH ‐mutated ones. Furthermore, IDH ‐SG exhibits less T cell infiltration and lower T cell cytotoxicity, indicating a colder tumor microenvironment (TME). The higher ITH and colder TME of IDH ‐SG are successfully validated by single‐cell RNA sequencing on 17 503 cells from 4 patients. Collectively, the study shows that IDH mutant subgroup status, rather than IDH mutation alone, is associated with ITH and the TME of ICC tumors. The results highlight that IDH ‐like patients may also benefit from IDH targeted therapies and provide important implications for the diagnosis and treatment of ICC. Abstract : Extensive intratumor heterogeneity (ITH) is observed in intrahepatic cholangiocarcinoma across genomic, transcriptomic, and immune levels. isocitrate dehydrogenase ( IDH ) mutation subgroup ( IDH‐ SG) exhibits higher ITH and colder tumor microenvironment. IDH ‐like patients may also benefit from IDH targeted therapies and caution should be made for its therapeutic selection. The study highlights the importance of evaluating IDH‐ SG status in future clinical management.